“University stress” exploring the potential impact of an immersive art experience on a college campus - Godley, Lyn; O’Hayer, C. Virginia; Davis, Raegan; Wakschal, Emily; Nurse, Chelsi; Ross, Wendy; Spraker, Abigail; Godshall, Nate; Frasso, Rosemary (Frontiers in Psychology, 2025)
There is growing interest in the effects of immersive art on wellbeing, which engages multiple senses and facilitates deeper engagement. University settings, particularly during high-stress periods like exams, are increasingly emphasizing mental health interventions to combat rising rates of anxiety, depression, stress, and suicidal ideation. This study investigates the potential of a fully immersive art experience to positively impact mood and reduce stress in a university setting. Pre- and post-visit questionnaires, including the Positive and Negative Affect Schedule (PANAS) survey, were administered to assess emotional changes. Additional open-ended questions provided qualitative feedback. Results showed statistically significant decreases in 12 negative affect scores and increases in 9 positive affect scores. Overall PANAS scores increased by a median of 6 points, indicating improved mood post-experience. Qualitative data highlighted the exhibit’s calming and restorative effects; many participants suggested amending the availability of such installations to a year-round schedule, in order to further promote student mental health.